The Development of Fishpreneurship to Build Entrepreneurial Interest For Muhammadiyah Magelang Polytechnic Students In The Face of The Covid-19 Pandemic - Rr. Citra Permata Kusuma Anggraini; Rachmat Subarkah (Agrikan: Jurnal Agribisnis Perikanan, 2022)
The Covid-19 pandemic has an impact on the employment sector, namely layoffs for workers. One of the efforts that can be done to survive this pandemic is by entrepreneurship. Universities have a role to prepare graduates who can entrepreneurship. Fishpreneurship is the development of fisheries-based entrepreneurial learning methods that aim to grow and know its influence on entrepreneurial interests for Muhammadiyah Magelang Polytechnic students. The method used in this study is a participatory learning action system (PLAS) with several stages, namely the awareness phase, mentoring phase, and institutionalization phase. This research was conducted from May to September 2021 located at Muhammadiyah Magelang Polytechnic. Entrepreneurial learning media by using catfish cultivation in buckets starting from seed spreading, maintenance to harvesting, and marketing. The type of catfish used is the pearl catfish Clarias gariepinus. Catfish cultivation in a bucket carried out for 69 days produces an absolute weight of 66.88 grams, SGR 96.92%, FCR 0.86, SR 93.33%, and an absolute length of 9.73 cm. The institutionalization phase is done by appointing students to become members of the Student Activity Unit (UKM) Polimmag Preneur which was formed to provide a platform for students to conduct fisheries-based entrepreneurial activities. This study concludes that fishpreneurship can foster entrepreneurial interest for Muhammadiyah Magelang Polytechnic students.